Diseño de un sistema de gestión basado en el balanced scorecard y planificación estratégica a una empresa de servicio, dedicada al hospedaje, ubicada en la ciudad de Guayaquil. - Peralta Cedeño, Katty Susana (2011)
This project will implement a management system based on Balanced Scorecard and strategic planning methodology to a service hosting company, located at north of the city, in the year 2009. The project consists of three fundamental chapters so the company can achieve its goals through indicators that help to measure and improve the situation. In the first chapter we will concern about Balanced Scorecard methodology and some important definitions to be used for the development of the project. Second chapter spoke about important description of the company and other points. The third chapter, which includes development of research, study and determine indicators for management and deployment system.